1997
DOI: 10.1007/s004360050256
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Blastocystis hominis infection in laboratory mice

Abstract: Young (less than 8 weeks old) immunocompetent BALB/c mice became infected with Blastocystis hominis after inoculation of fecal cysts orally and of in vitro axenic-culture forms intracecally. This study confirmed that the fecal cyst was the form responsible for external transmission and that the mode of transmission was by the fecal-oral route. The infection was self-limiting and the infected BALB/c mice appeared normal except that some of them showed weight loss and lethargy. Both vacuolar and granular forms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 13 publications
8
92
0
Order By: Relevance
“…Animal models exist to study the most common enteric protozoa. Experimental infection of mice and rats with Blastocystis isolates found in humans has been reported to produce illness or death in a number of independent studies (Moe et al 1997, Yao et al 2005, Zhang et al 2006, Hussein et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models exist to study the most common enteric protozoa. Experimental infection of mice and rats with Blastocystis isolates found in humans has been reported to produce illness or death in a number of independent studies (Moe et al 1997, Yao et al 2005, Zhang et al 2006, Hussein et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…The cyst represents the smallest (2 to 5 m in diameter) form of the organism and is responsible for the environmental dissemination of the parasite. The results of in vivo experiments previously performed with mice have suggested that cysts represent the infectious stage (18,35,37), but the most common form detected during parasitological examination of feces is the vacuolar form (2 to 200 m in diameter) (41,44). The vacuolar form also represents the major parasitic stage observed in in vitro cultures of Blastocystis parasites.…”
mentioning
confidence: 96%
“…There are no reports of Blastocystis-associated dysentery, and it appears that the parasite is generally noninvasive, as indicated by endoscopy (43,76,329,330) and histology of experimentally infected animals (5,152,187). An interesting case study described Blastocystis trophozoites present in the liver abscess aspirate of a 63-year-old man with a 5-day history of fever and blood-tinged watery diarrhea (102).…”
Section: Infection and Diseasementioning
confidence: 99%
“…Heavy infections led to diarrhea and gross cecal hyperemia. A later study involved the experimental infection of young (less than 8 weeks old) BALB/c mice with Blastocystis (152). Infections were generally self-limiting, although some mice showed weight loss, and histological examination revealed inflammatory responses and mucosal sloughing.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation